The West Mediterranean Alona azorica Frenzel & Alonso, 1988 (Cladocera: Anomopoda: Chydoridae) is composed of two species - Sinev, Artem Y.; Alonso, Miguel; Miracle, Maria Rosa; Sahuquillo, Maria (Zootaxa, 2012)
A study of several populations of the West Palaearctic endemic Alona azorica Frenzel & Alonso, 1988 reveals the exis-tence of a sibling-species. Alona azorica s. str. is confined to the Azores and the Atlantic part of West Iberia; Alona anas-tasia sp. nov. inhabits temporary ponds in Mediterranean Iberia and other West Mediterranean regions. It differs by size,by the morphology of the head shield and head pores, and by the shape of the male postabdomen. Both species belong tothe pulchella-group of Alona s. lato. Alona anastasia sp. nov. population dynamics and seasonal variation in body size in the province of Valencia (Spain) are also studied.